2000
DOI: 10.1038/sj.onc.1203338
|View full text |Cite
|
Sign up to set email alerts
|

Motility and invasion are differentially modulated by Rho family GTPases

Abstract: Cell migration in vivo often requires invasion through tissue matrices. Currently little is known regarding the signaling pathways that regulate cell invasion through three-dimensional matrices. The small GTPases Cdc42, Rac and Rho are key regulators of actin cytoskeletal and adhesive structures. We now show that expression of dominant negative forms of either Cdc42, Rac or Rho inhibited PDGF-BB-stimulated Rat1 ®broblast invasion into 3D collagen matrices, indicating that the activity of each of these GTPases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
94
4
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(113 citation statements)
references
References 62 publications
14
94
4
1
Order By: Relevance
“…However, these results are contradictory to the results with RNA interference of MMP-9, which show that RhoA is inactive in the presence of MMP-9 and inhibition of MMP-9 expression decreases cell spreading (Sanceau et al, 2003). It has been shown that inhibition of Rho by overexpression of a dominant negative mutant inhibits invasion but as well overexpression of Rho reduces invasiveness (Banyard et al, 2000). These contradictory results may be explained by the finding that fluctuating levels of active Rho, rather than constitutively active Rho, are required for efficient invasion (Lin et al, 1999).…”
Section: Multiple Roles Of Proteinases In Cell Migration and Invasioncontrasting
confidence: 53%
“…However, these results are contradictory to the results with RNA interference of MMP-9, which show that RhoA is inactive in the presence of MMP-9 and inhibition of MMP-9 expression decreases cell spreading (Sanceau et al, 2003). It has been shown that inhibition of Rho by overexpression of a dominant negative mutant inhibits invasion but as well overexpression of Rho reduces invasiveness (Banyard et al, 2000). These contradictory results may be explained by the finding that fluctuating levels of active Rho, rather than constitutively active Rho, are required for efficient invasion (Lin et al, 1999).…”
Section: Multiple Roles Of Proteinases In Cell Migration and Invasioncontrasting
confidence: 53%
“…Although transient transfection of Rac (61L): GFP caused a dramatic increase in ruffle activity, cells still could not migrate (unpublished data). However, we do not believe this result is inconsistent with our model because expression of constitutively activated Rac can both increase and decrease migration, depending on the cell type and assay used (Leng et al, 1999;Banyard et al, 2000;Ridley, 2001b). An explanation for our result may be that expression of activated Rac localizes Rac in a nonpolar manner, so the cell cannot move because it is trying to protrude in every direction (Allen et al, 1998).…”
Section: R-ras Regulates Cell Migrationcontrasting
confidence: 48%
“…Our results might, therefore, indicate that RhoA is not required for cell motility [see also Banyard et al, 2000]. However, other reports indicate that activation of Rho is necessary for the motile behavior of cells [Stasia et al, 1991;Takaishi et al, 1994;Ridley et al, 1995;Santos et al, 1997;Nobes and Hall, 1999].…”
Section: Discussionmentioning
confidence: 58%